Brand Storytelling and It’s Influence Towards Building Consumer-Brand Identification, Brand Attitude, and Purchase Intention in Cosmetics: A Case Study in A Local Skincare Brand - Athalla, Giva; Fachira, Ira (Journal of Business and Management, 2021)
With the ever-growing advancements and significance of technology in today’s generation of consumer and ease of access to millions of brands, brands use a story to distinguish themselves. Cosmetic brands in particular are known to use storytelling to attract their consumers as it caters to their psychological needs—their own definitions and perceptions of beauty—making it personal to the consumers. Using digital storytelling, brands can defy conventional sense of storytelling by using different stimuluses such as videos which, if broken down, is essentially a collection of images, sounds and even texts. This study aims to explore how these brands use Brand Story to build their audiences to gain favorable Brand Attitude, Consumer-Brand Identification and Purchase Intention. Using an experimental approach studying how a cosmetic brand (Skin Game) affects their audience by using a video to tell their story. The results indicate brand story has a significant positive influence on brand attitude as well as brand attitude towards purchase intention. However, this study did not identify a significant influence of brand story and brand attitude towards consumer-brand identification. The results of this study share insights and are expected to make a contribution in theoretical and practical implications in digital storytelling for cosmetic brands.Keywords: Cosmetics, Digital Storytelling, Brand Story, Consumer-Brand Identity, Brand Attitude, Purchase Intention